Multilevel population-based cross-sectional study examining school substance-misuse policy and the use of cannabis, mephedrone and novel psychoactive substances among students aged 11–16 years in schools in Wales. Issue 6 (14th June 2018) - Midgley, Luke S; Murphy, Simon; Moore, Graham; Hewitt, Gillian; White, James
Abstract : Objectives: To examine whether young peoples' risk of cannabis, mephedrone and novel psychoactive substances (NPS) use is associated with school substance-misuse policy. Design: A cross-sectional survey of secondary school students combined with a School Environment Questionnaire and independently coded school substance-misuse policies (2015/6). Setting: 66 secondary schools in Wales. Participants: Students aged 11–16 years (n=18 939). Results: The prevalence of lifetime, past 30-day and daily cannabis use was 4.8%, 2.6% and 0.7%, respectively; lifetime prevalence of mephedrone use was 1.1% and NPS use was 1.5%. Across 66 schools, 95.5% (n=63) reported having a substance-misuse policy, 93.9% (n=62) reported having a referral pathway for drug using students, such that we were insufficiently powered to undertake an analysis. We found little evidence of a beneficial association between lifetime cannabis use and involving students in policy development including student council consultation (OR=1.24, 95% CI 0.89 to 1.73), other student consultation (OR=1.42, 95% CI 0.94 to 2.14) or with the use of isolation (OR=0.98, 95% CI 0.67 to 1.43), with similar results for cannabis use in past 30 days, daily and the lifetime use of mephedrone and NPS. The School Environment Questionnaires found that 39.4% (n=26) schools reported no student involvement in policy development, 42.4% (n=28) reported student council consultation, 18.2% (n=12) used other student consultations and 9.7% (n=3) mentioned isolation. The independently coded content of policies found that no school policy recommended abstinence, one mentioned methods on harm minimisation, 16.1% (n=5) policies mentioned student involvement and 9.7% (n=3) mentioned isolation. Conclusions: Policy development involving students is widely recommended, but we found no beneficial associations between student involvement in policy development and student drug use. This paper has highlighted the need for further contextual understanding around the policy-development process and how schools manage drug misuse.